2022
DOI: 10.1159/000525542
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillary Glomerulonephritis, DNAJB9, and the Unfolded Protein Response

Abstract: Background: Fibrillary glomerulonephritis (FGN) is found in approximately 1% of native kidney biopsies and was traditionally defined by glomerular deposition of fibrils larger than amyloid (12-24nm diameter) composed of polyclonal IgG. Recent identification of DNAJB9 as a sensitive and specific marker of FGN has revolutionized FGN diagnosis and opened new avenues to studying FGN pathogenesis. In this review, we synthesize recent literature to provide an updated appraisal of the clinical and pathologic feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The identification of DNAJ homolog subfamily B member 9 (DNAJB9), a co-chaperone of the heat-shock protein 70 family members, which was first related to FGN in 2017, now serves as a 98% sensitive and, according to recent studies, 100% specific FGN biomarker. It is found in all biopsy specimens and almost 80% of the suspected cases [ 16 , 17 ]. DNAJB9 is mainly an intracellular protein, normally found in the endoplasmic reticulum of all cellular types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of DNAJ homolog subfamily B member 9 (DNAJB9), a co-chaperone of the heat-shock protein 70 family members, which was first related to FGN in 2017, now serves as a 98% sensitive and, according to recent studies, 100% specific FGN biomarker. It is found in all biopsy specimens and almost 80% of the suspected cases [ 16 , 17 ]. DNAJB9 is mainly an intracellular protein, normally found in the endoplasmic reticulum of all cellular types.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested that rituximab therapy alone or with simultaneous steroid intake offers a non-progression in kidney function in a 12-month observation and a satisfactory reduction in 24-hour proteinuria [ 19 ]. However, no case of complete remission after rituximab therapy was recorded [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation